Equilibrium versus understanding : towards the restoration of economics as social theory - Addleson, Mark (Routledge frontiers of political economy ;, 1995)
Neo-classical theory is incapable of explaining or understanding human conduct. The author favours an interpretative approach to social theory, providing a novel critique of equilibrium theory and insight into the nature of business decisions.